2017
DOI: 10.1002/jcc.24821
|View full text |Cite
|
Sign up to set email alerts
|

Excited‐state minima and emission energies of retinal chromophore analogues: Performance of CASSCF and CC2 methods as compared with CASPT2

Abstract: This study provides gas-phase S excited-state geometries along with emission and adiabatic energies for methylated/demethylated and ring-locked analogues of protonated Schiff base retinal models comprising system of five conjugated double bonds (PSB5), using second order multiconfiguration perturbation theory (CASPT2). CASPT2 results serve as reference data to assess the performance of CC2 (second-order approximate coupled cluster singles and doubles) and a commonly used CASSCF/CASPT2 protocol, that is, comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 82 publications
(182 reference statements)
3
12
0
Order By: Relevance
“…Also, in our recent study on PSB3 (a minimal model of RPSB with three double bonds), we noticed more pronounced double‐single bond length alternation in CASSCF ground‐state structures with respect to the third‐order corrected perturbation theory (CASPT3) and coupled cluster (CCSD(T)) data. Interestingly, a quite successful performance of CASSCF was found in the S 1 excited state of PSB5 analogs as geometrical features of S 1 true minima are well in line with CASPT2 results …”
Section: Introductionsupporting
confidence: 70%
See 2 more Smart Citations
“…Also, in our recent study on PSB3 (a minimal model of RPSB with three double bonds), we noticed more pronounced double‐single bond length alternation in CASSCF ground‐state structures with respect to the third‐order corrected perturbation theory (CASPT3) and coupled cluster (CCSD(T)) data. Interestingly, a quite successful performance of CASSCF was found in the S 1 excited state of PSB5 analogs as geometrical features of S 1 true minima are well in line with CASPT2 results …”
Section: Introductionsupporting
confidence: 70%
“…In our view more studies on the excited state of various retinal systems are needed to draw general conclusions on the range of suitability of CC2 method in this field. In fact, we have recently shown that CC2 provides excited‐state geometries and emission energies for chosen PSB5 analogs in line with state‐of‐the‐art CASPT2 results for in‐plane models . Nonetheless, this good agreement usually deteriorates for twisted excited‐state minimum‐energy structures near the FC point …”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…Since CC2 methodology has been often utilized in spectroscopic studies of excited states in biochromophores we assess its performance here with respect to the experimental AM and theoretical best estimates. By analyzing the results in Table , one can notice that the CC2 performance in reproducing AM is not as impressive as the one by XMCQDPT2.…”
Section: Resultsmentioning
confidence: 99%
“…Even more, for a series of RPSB models ranging from PSB3 to PSB5 (model containing five conjugated double bonds) and also for full RPSB chromophore, S‐IPEA outperforms 0‐IPEA and provides results in close agreement with quantum Monte Carlo results . Of course, there are other factors, besides the IPEA shift value, that may contribute to the CASPT2‐based vertical excitation energy error such as basis set size, the selection, and size of the active space, number of roots in the SA‐CASSCF wave function, value of level shift parameter, and the quality of the equilibrium geometry . However, among the aforementioned factors affecting vertical excitation energies (VEEs), the IPEA shift parameter does affect the excitation energies to the largest extent provided that the basis set and active space are sufficiently large.…”
Section: Introductionmentioning
confidence: 82%